Music performance: another debate regarding the interpreter and academia (Orfeu, 2022)
Discussion regarding Brazilian’s interpreters and performers in the university and academia. Method is focused on bibliographical review with works from national and international researches related to the main topic, also with interdisciplinary approaches. Conclusions point to the implementation of artistic research, more specifically research through arts (BORGDORFF, 2012) and its necessary infrastructure, aiming to finally legitimate the interpreter’s position in Brazilian’s academic field.
Keywords: Music Performance; Scientific methodology; Artistic Research; Research through Arts